Interpreting the historical books an exegetical handbook - Chisholm, Robert B. (Grand Rapids, MI Kregel, 2006)
Contents : What is narrative literature? -- Primary themes of the historical books -- Preparing for interpretation -- Interpretating narrative texts -- Proclaiming narrative texts -- From text to apllication: two samples. Includes biliographical references.
Keywords: Bible. O.T. Historical Books -- criticism, interpretation, etc